COVID-19 mimicked fetal hemolytic disease: a case report - Lakhno, Igor (Publishing House Professional Event, 2023)
The pandemic of COVID-19 changed the traditional approaches to the management of gestational complications. Today there is still a lack of information about the impact of COVID-19 on the pregnancy course, in particular, about its role in relation to Rh-conflict during pregnancy. The paper focused on a rare presentation of Rh-conflict pregnancy and COVID-19. 32 years old G3 P2 pregnant women with Rh-negative had a third pregnancy. The injection of anti-D immunoglobulin after the first abortion was not performed. The second pregnancy finished with a term delivery and the birth of a fetus with hemolytic disease. During the third pregnancy, the woman fell ill with COVID-19 in the 26th week. The bilateral pneumonia was diagnosed. The treatment included antibiotics, antiviral, antithrombotic, and anti-inflammatory drugs. No signs of fetal hemolytic disease were found via ultrasonography. But the abnormal level of anti-D antibodies – 1:1024 was detected. From the 28th weeks of pregnancy till the delivery the test for anti-D antibodies was constant – 1:4. The variables of utero-placental, fetal (blood flow velocity in a middle cerebral artery), and umbilical hemodynamics were normal during the third trimester. But fetal moderate hepato- and splenomegaly were found at 36 weeks of gestation. The patient delivered at 38 weeks of gestation a female newborn 3100 g, 52 cm with a 7→8 Apgar score. The laboratory investigation detected a hemoglobin value of 202.6 mg/dL in a child. The blood analysis showed total bilirubin of 44.2 mg/dL, direct bilirubin of 1.0 mg/dL, and a negative result on the direct Coombs test. The baby received phototherapy for 3 days. Total bilirubin was decreased (15.2 mg/dL). The newborn was discharged from a hospital with the mother on the fifth day. COVID-19 could change the placental permeability and increase the titer of anti-D antibodies. But it did not contribute to fetal and newborn hemolytic disease.
Keywords: COVID-19; pregnancy; hemolytic disease of the fetus and newborn; placental barrier